2019
DOI: 10.1186/s12876-019-1038-5
|View full text |Cite
|
Sign up to set email alerts
|

Anemia following zinc treatment for Wilson’s disease: a case report and literature review

Abstract: Background Zinc therapy is considered an effective and safe treatment for Wilson’s disease. Hypocupremia-related anemia is rarely reported after long-term zinc administration or combination therapy with copper-chelating agent. Case presentation We herein report a 12-year-old girl with pre-symptomatic Wilson’s disease diagnosed 5 years ago who presented with severe anemia after high-dose oral zinc for 4 years and 4 months. Her hemoglobin was gradually restored to the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Nevertheless, rare cases of gastrointestinal reactions and hepatic deterioration can occur during zinc therapy [83][84][85]. Up to now, eight patients with anemia after a long period of zinc therapy for WD have been reported [86], thus regular follow-up during zinc treatment and the involvement of specialists in the long-term management of Wilson's disease are recommended.…”
Section: Zinc In the Therapy Of Wilson's Diseasementioning
confidence: 99%
“…Nevertheless, rare cases of gastrointestinal reactions and hepatic deterioration can occur during zinc therapy [83][84][85]. Up to now, eight patients with anemia after a long period of zinc therapy for WD have been reported [86], thus regular follow-up during zinc treatment and the involvement of specialists in the long-term management of Wilson's disease are recommended.…”
Section: Zinc In the Therapy Of Wilson's Diseasementioning
confidence: 99%
“…Hypocupremia with zinc preparations has also been reported in Wilson's disease, a copper overload disorder. (28) Poor prognosis has also been reported in cases where serum zinc has not improved after zinc supplementa-tion. (26) Although zinc has been studied for many years, there is still a lack of evidence about effective ways to improve zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…An interaction between metals, such as zinc/ copper and zinc/ iron, has been widely reported in the past. In the case of copper for example, there are several reports in the clinical literature where zinc supplementation in coeliac disease, sickle cell anemia, acrodermatitis enteropathica and Wilson's disease results (potentially via an effect on proteins such as metallothionein) in severe copper deficiency [34][35][36][37]. Similarly, a study in Caco-2 cells demonstrated that there is an inverse relationship between zinc and iron such that increased levels of extracellular zinc applied to the cells results in decreasing intracellular iron levels [38].…”
Section: Discussionmentioning
confidence: 99%